Structural assessment of jet impingement loads under postulated main steam line break conditions. (May 2018) - Kim, Seung Hyun; Chang, Yoon-Suk; Choi, Dae Kyung; Choi, Choengryul
Highlights: A numerical methodology was suggested for realistic structural integrity assessment under HELB conditions. Effects of jet impingement loads from a representatively postulated main steam line break were quantified. Assessment results by the proposed methodology were compared with those by ANSI/ANS-58.2 standard. Abstract: When a sudden rupture occurs in high energy lines, the ejection of inner fluid with high temperature and pressure causes jet impingement loads on adjacent components and structures, as well as on the ruptured pipe itself. This study examines the jet impingement phenomenon under postulated HELB (High Energy Line Break) conditions. In this context, typical numerical models were generated considering the SG (Steam Generator), MSL (Main Steam Line) piping, and containment. Subsequently, two sets of numerical analyses were carried out by changing the break locations. One set is computational fluid dynamics to assess the ejected fluid characteristics and define pressure histories. The other uses finite element analyses to calculate the stresses and displacements of the SG, piping, and containment building caused by the jet impingement loads. As a result, detailed analyses provided more realistic and conservative data than those in the ANSI/ANS 58.2 standard used in the current HELB design while the jet loads did not threat secondary structural integrity after the MSL piping break.